2006
DOI: 10.1016/j.febslet.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, inhibition and oligomerization of Epstein‐Barr virus protease

Abstract: Epstein-Barr virus (EBV) is an omnipresent human virus causing infectious mononucleosis and EBV associated cancers. Its protease is a possible target for antiviral therapy. We studied its dimerization and enzyme kinetics with two enzyme assays based either on the release of paranitroaniline or 7-amino-4-methylcoumarin from labeled pentapeptide (Ac-KLVQA) substrates. The protease is in a monomer-dimer equilibrium where only dimers are active. In absence of citrate the K d is 20 lM and drops to 0.2 lM in presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It has been established in other proteases that catalytic function is dependent on dimerization. For example, the catalytic ability of the Epstein-Barr protease has previously been shown to be dependent on the extent of dimerization (11), and HIV-1 protease oligomerization inhibitors are currently in development (12).…”
mentioning
confidence: 99%
“…It has been established in other proteases that catalytic function is dependent on dimerization. For example, the catalytic ability of the Epstein-Barr protease has previously been shown to be dependent on the extent of dimerization (11), and HIV-1 protease oligomerization inhibitors are currently in development (12).…”
mentioning
confidence: 99%
“…HPLC-grade solvents were used for HPLC and LC/MS analyses. The Fmoc-protected norstatine analogue of alanine [(3S)-3-{[(9H-fluoren-9-ylmethoxy)carbonyl]amino}-2-hydroxybutanoic acid], which was used as the precursor of the -ketoacyl residue, was synthesized from Fmoc-Ala-OH as described previously (Buisson et al, 2006).…”
Section: Synthesis Of Mam-117 An A-ketoamide Inhibitor Of Pvs1mentioning
confidence: 99%
“…Biochemical and x-ray crystallography studies revealed that EBV PR is active as a homodimer. Dimerization is crucial for the stabilization of the active site in each of the monomers [25,[27][28][29]. The EBV PR, present in mature virions, could elicit a specific T-cell-mediated immune response in vivo [21,30].…”
Section: Original Articlementioning
confidence: 99%